Mali : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper assesses the distributional effects of increased fuel prices on Mali. The paper applies cointegration analysis to simulate the evolution of Mali's long-term equilibrium real exchange rate during the period 1982-2004. It assesses the impact of structural reforms on Mali's aggregate output growth, using a growth accounting framework that disaggregates output growth into factor accumulation and total factor productivity (TFP). The paper also explores the scope for creating and using fiscal space over the medium term under a range of illustrative policy scenarios.